Role of ICTs in Promoting Learner Independence and Motivation in English Language Classes - Joshi, Khem Raj; Poudel, Guru Prasad (Interdisciplinary Research in Education, 2019)
This article builds up on an action research which was carried out mainly with two major purposes: to investigate learner perceptions and attitudes in the use of ICTs in English language classes; and to examine the role of ICTs in promoting the learner independence and motivation. The population of the study consisted of all the students from the Department of English Education, Central Department of Education, Kirtipur. The area was purposively selected; we have been teaching in the same place for seven years. The participants were 37 students who were also purposively selected. Among them, only 15 students were invited to a focused group discussion (FGD). However, all the students participated in the intervention for the whole semester. The intervention was implemented during the instruction. The major ICT tools adopted for the study were: web sites, e-mails and multimedia. We administered three progress tests to assess their progress in terms of independence and motivation. The findings of this research show that the learners are well motivated and positive in the use of ICTs in language teaching.